Vitamin B12 and Folate as Risk Factors for Retinal Vein Occlusion: A Meta-Analysis - Kazantzis, Dimitrios; Theodossiadis, Panagiotis; Kroupis, Christos; Theodossiadis, George; Chatziralli, Irini (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To evaluate the association between serum vitamin B12/folate and retinal vein occlusion (RVO).Methods A comprehensive search of the PubMed database was performed, which identified 271 abstracts to be screened. Ten studies met our inclusion criteria and a meta-analysis of these comparative case-control studies was performed on the mean ± standard deviation serum vitamin B12 and folate levels, without language restrictions. Nine studies with 720 patients with RVO and 613 controls were included in the meta-analysis for vitamin B12, and 10 studies with 784 patients with RVO and 677 controls in the meta-analysis for folate.Results There was no statistically significant difference between patients with RVO and controls in serum vitamin B12 levels (mean difference: − 40.25 pg/mL, p = 0.28), either central RVO (mean difference: − 18.24 pg/mL, p = 0.71) or branch RVO (mean difference: − 23.56 pg/mL, p = 0.48). On the contrary, the plasma folate level was significantly lower in RVO patients than in controls (mean difference: − 1.34 ng/mL, p = 0.001), as well as in patients with CRVO compared to controls (mean difference: − 1.48 ng/mL, p = 0.006), but not in BRVO patients (mean difference: − 0.72 ng/mL, p = 0.11).Conclusions RVO is associated with low serum folate levels, but not with serum vitamin B12 levels.
Keywords: retinal vein occlusion; vitamin B12; B9; folate